2008
DOI: 10.1089/cap.2007.053
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal Cortex Volumes in Medication Naïve Children with Major Depressive Disorder: A Magnetic Resonance Imaging Study

Abstract: The lack of OFC volume abnormalities in pediatric MDD patients suggests the abnormalities previously reported for adults may develop later in life as a result of neural cell loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Based on prior research showing reduced volume of the orbitofrontal cortex (OFC) in adults with MDD, Chen and colleagues (2008) examined OFC volumes in medication naïve adolescents with MDD and controls. Authors reported no significant differences in total OFC volume or OFC gray matter volume, but exploratory analyses revealed that patients had larger total and gray matter volumes of the right lateral subregion of the OFC.…”
Section: Results: Neuroimaging Findings In Child and Adolescent Majormentioning
confidence: 99%
See 1 more Smart Citation
“…Based on prior research showing reduced volume of the orbitofrontal cortex (OFC) in adults with MDD, Chen and colleagues (2008) examined OFC volumes in medication naïve adolescents with MDD and controls. Authors reported no significant differences in total OFC volume or OFC gray matter volume, but exploratory analyses revealed that patients had larger total and gray matter volumes of the right lateral subregion of the OFC.…”
Section: Results: Neuroimaging Findings In Child and Adolescent Majormentioning
confidence: 99%
“…Authors reported no significant differences in total OFC volume or OFC gray matter volume, but exploratory analyses revealed that patients had larger total and gray matter volumes of the right lateral subregion of the OFC. It was suggested that the findings of decreased volume in OFC found in adult MDD may be related to neural loss that occurs later in life (Chen, Rosenberg et al 2008). …”
Section: Results: Neuroimaging Findings In Child and Adolescent Majormentioning
confidence: 99%
“…It is, however, important to mention that not all structural imaging studies have reported PFC changes in adolescent depression. For example, an earlier ROI-based study failed to observe a significant difference in OFC volume between depressed adolescents and controls (Chen et al 2008). These conflicting results might be due to methodological differences between the VBM and ROI-based approaches.…”
Section: Shad Et Almentioning
confidence: 90%
“…Specifically, OFC gray matter deficits are commonly observed in young adult and elderly patients with affective disorders (54-60) but not in firstepisode (72) or adolescent patients with affective disorders (73,74). A recent 2-y longitudinal study found that OFC gray matter volume reductions during adolescence were accelerated in bipolar patients compared with healthy subjects (75). In this study, the relative OFC gray matter volume loss in typical adolescents (0.33%/y) was increased 5-fold in bipolar patients (1.8%/y).…”
Section: Neuropathology In Affective Disordersmentioning
confidence: 99%